Uji Aktivitas Immunomodulator Berbagai Tanaman Famili Piperaceae pada Mencit Galur Balb/C dengan Metode Carbon Clearance - Mohammad Roseno; Yayat Sudaryat; Widyastiwi Widyastiwi (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Plants of Piperaceae family are widespread in the tropics region and have been widely used as medicinal plants, these includes kemukus (Piper cubeba), kiseureuh (Piper aduncum), and Java chili (Piper retrofractum). The purpose of this study was to evaluate the immunomodulatory activity of ethanol extracts of several plants from the Piperaceae family in Balb/C strain mice with carbon clearance method. The study was conducted by dividing the experimental animals into 12 groups : normal control group, immunosuppressant comparison, immunostimulant comparison, and low, moderate, and high dose of kemukus, kiseureuh, and Java chili, resepctively. Immunomodulatory activity was measured by phagocytosis index, peripheral blood leukocyte levels, and splenic leukocyte levels. The results showed that ethanol kemukus extract (Piper cubeba) acts as an immunosuppressant, increasing the dose increased the immunosuppressant effect. Low doses of ethanol extract of kiseureh (Piper aduncum) also acts as immunosuppressant, whereas at medium and high doses has a tendency to be immunostimulant. Ethanol extract of Java chili (Piper retrofractum) acts as an immunostimulant, with the highest activity achieved at moderate doses. Ethanol extract of kemukus (Piper cubeba), kiseureh (Piper aduncum), and Java chili (Piper retrofractum) affect the number of peripheral blood granulocyte components, neutrophils levels affects the increase in phagocytic effects. Ethanol extract of kemukus (Piper cubeba), kiseureh (Piper aduncum), and Java chili (Piper retrofractum) did not affect the number of splenic blood granulocyte components.